Efficacy of a surfactant‐based wound dressing on biofilm control. Issue 5 (11th October 2017) - Percival, Steven L.; Mayer, Dieter; Salisbury, Anne‐Marie
Abstract: The aim of this study was to evaluate the efficacy of both a nonantimicrobial and antimicrobial (1% silver sulfadiazine—SSD) surfactant‐based wound dressing in the control of Pseudomonas aeruginosa, Enterococcus sp, Staphylococcus epidermidis, Staphylococcus aureus, and methicillin‐resistant S. aureus (MRSA) biofilms. Anti‐biofilm efficacy was evaluated in numerous adapted American Standards for Testing and Materials (ASTM) standard biofilm models and other bespoke biofilm models. The ASTM standard models employed included the Minimum biofilm eradication concentration (MBEC) biofilm model (ASTM E2799) and the Centers for Disease Control (CDC) biofilm reactor model (ASTM 2871). Such bespoke biofilm models included the filter biofilm model and the chamberslide biofilm model. Results showed complete kill of microorganisms within a biofilm using the antimicrobial surfactant‐based wound dressing. Interestingly, the nonantimicrobial surfactant‐based dressing could disrupt existing biofilms by causing biofilm detachment. Prior to biofilm detachment, we demonstrated, using confocal laser scanning microscopy (CLSM), the dispersive effect of the nonantimicrobial surfactant‐based wound dressing on the biofilm within 10 minutes of treatment. Furthermore, the non‐antimicrobial surfactant‐based wound dressing caused an increase in microbial flocculation/aggregation, important for microbial concentration. In conclusion, this nonantimicrobial surfactant‐based wound dressing leads to the effective detachment and dispersion of in vitro biofilms. The use of surfactant‐based wound dressings in a clinical setting may help to disrupt existing biofilm from wound tissue and may increase the action of antimicrobial treatment.